2022
DOI: 10.1111/jav.02913
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally impaired female condition does not affect biliverdin‐based egg colour

Abstract: It has been proposed that blue-green egg coloration is a condition-dependent female sexual trait that may modify paternal care in a post-mating sexual selection scenario. This pattern may arise because the pigment responsible for eggshell colouration (biliverdin) may be a costly and limited resource, whose availability is linked to female health state. Thus, it can be predicted that females whose condition is compromised should be constrained in their capacity to deposit biliverdin in the eggshell, thus produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Alternatively, the detected pattern may have also occurred if our original assumption was incorrect and pigmented eggs were not more expensive to produce than unpigmented white eggs (e.g. Hanley and Doucet 2009 ; Honza et al 2011 ; Krištofík et al 2013 ; D’Arpa et al 2022 ). Such possibilities are worthy of further research because, despite the correlative, comparative relationships between eggshell colouration and reproductive investment revealed here, their causal determinants remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the detected pattern may have also occurred if our original assumption was incorrect and pigmented eggs were not more expensive to produce than unpigmented white eggs (e.g. Hanley and Doucet 2009 ; Honza et al 2011 ; Krištofík et al 2013 ; D’Arpa et al 2022 ). Such possibilities are worthy of further research because, despite the correlative, comparative relationships between eggshell colouration and reproductive investment revealed here, their causal determinants remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of territorial dynamics in bird species is biased towards the behaviour of owners, whereas floaters, which are key actors in territory conflicts, are typically neglected. By experimentally reducing the flight performance of breeders of both sexes [ 19 ], we tested if male and female floaters preferentially prospected nests owned by manipulated breeders. We found that this was the case for male birds, since nests in which the male owner had been wing-clipped attracted a larger number of male floaters than control nests.…”
Section: Discussionmentioning
confidence: 99%
“…= 9.6) before egg laying. We previously reported that, after controlling for pre-treatment body weight, wing-clipped females were 3.1% lighter than controls while brooding (males could not be caught at this time, but we assume that a similar effect would occur) [ 19 ]. The initial sample size was 24 control nests, 19 nests with wing-clipped females and 25 with wing-clipped males.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation